2010
DOI: 10.2134/jeq2009.0027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Manure and Cultivation on Carbon Dioxide and Nitrous Oxide Emissions from a Corn Field under Mediterranean Conditions

Abstract: The use of organic residues as soil additives is increasing, but, depending on their composition and application methods, these organic amendments can stimulate the emissions of CO(2) and N(2)O. The objective of this study was to quantify the effects of management practices in irrigated sweet corn (Zea mays L.) on CO(2) and N(2)O emissions and to relate emissions to environmental factors. In a 3-yr study, corn residues (CR) and pasteurized chicken manure (PCM) were used as soil amendments compared with no resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 38 publications
9
34
0
Order By: Relevance
“…An annual CO 2 emission rate of 9.7 mg CO 2 -C ha -1 y -1 has been reported from corn treated with pasteurized chicken manure at a rate of 10 mg ha -1 yr -1 in sandy loam soil (Heller et al, 2010) and at 13.3-15.3 mg CO 2 -C ha -1 y -1 from cattle manure at a rate of 20 mg ha -1 (fresh weight) in sandy soil (Matsumoto et al, 2008). Fereidooni et al (2013) concluded that soil CO 2 -C production for fertilized and unfertilized plots over 20-day sampling times was similar, but was greater after the addition of urea and broiler litter than for the unfertilized plot at other sampling times.…”
Section: Resultsmentioning
confidence: 99%
“…An annual CO 2 emission rate of 9.7 mg CO 2 -C ha -1 y -1 has been reported from corn treated with pasteurized chicken manure at a rate of 10 mg ha -1 yr -1 in sandy loam soil (Heller et al, 2010) and at 13.3-15.3 mg CO 2 -C ha -1 y -1 from cattle manure at a rate of 20 mg ha -1 (fresh weight) in sandy soil (Matsumoto et al, 2008). Fereidooni et al (2013) concluded that soil CO 2 -C production for fertilized and unfertilized plots over 20-day sampling times was similar, but was greater after the addition of urea and broiler litter than for the unfertilized plot at other sampling times.…”
Section: Resultsmentioning
confidence: 99%
“…Under similar conditions Collins et al (2011) reported little difference in C emissions from liquid manure-treated soils. By contrast, manure increased CO 2 emissions twofold when added to corn systems harvested for grain, which retained all corn stover residue in the field (Adviento-Borbe et al, 2010;Heller et al, 2010). The total seasonal DOC output via irrigation runoff was greater for manure than control treatments in 2004 (Table 5) due primarily to one significantly greater runoff DOC n event for manure vs. control furrows (Fig.…”
Section: Carbon Balancementioning
confidence: 96%
“…However, Robbins (1986) and Heller et al (2010) have shown that manure additions can increase CaCO 3 solubility and leaching in soils by increasing soil respiration and CO 2 partial pressures, and by increasing soil organic acid concentrations. Finlay (2003) found that DIC concentrations in surface streams can be influenced by both geochemical and biotic factors.…”
mentioning
confidence: 99%
“…Previous research indicates that manure application commonly increases soil CO 2 -C emissions, with the magnitude dependent on manure rate, current crop and residue return rate, and previous crop residue (Gregorich et al, 1998;Drury et al, 2008;Adviento-Borbe et al, 2010;Heller et al, 2010;Shrestha et al, 2013). In the current study, the 1.2-fold increase in CO 2 -C emissions for manure relative to no-manure treatments matched that observed in a corn-small-grain rotation after livestock manure (at a rate similar to ours) was applied to an Alberta, Canada field (Ellert and Janzen, 2008).…”
Section: Manure Effectsmentioning
confidence: 99%